Dual targeting of CXCR4 and EZH2 in endometriosis - Sarah Brunty; Kassey Wagner; Taylor Fleshman; Morgan Ruley; Brenda Mitchell; Nalini Santanam (iScience)
Summary: We recently showed that endometriotic peritoneal fluid (PF) altered the regulation of enhancer of zeste homolog 2 (EZH2) and H3K27me3. This study aimed to determine if PF by regulating EZH2/H3K27me3 modulated C-X-C chemokine receptor type 4 (CXCR4), a major chemokine involved in the proliferation and migration processes in endometriosis. Endometriotic PF induced the mRNA expression of CXCR4 and EZH2 and protein expression of H3K27me3 in human endometrial stromal cells (hESCs) and eutopic endometrium (Eu). CXCR4 inhibitor, AMD3100, decreased the PF-induced expression of these factors and reduced migration, but increased the proliferation of hESCs. In contrast, the EZH2 inhibitor, GSK126, decreased the expression of EZH2 and H3K27me3 and reduced proliferation, but increased the expression of CXCR4 and migration of hESCs. A combination of both inhibitors decreased the expression of CXCR4, EZH2, and H3K27me3, as well as reduced cell proliferation and migration. Our study suggests that targeting both CXCR4 (inflammation) and EZH2 (epigenetics) may be a better alternative for women with endometriosis.